Lego awesome ideas - Lipkowitz, Daniel (DK Publishing, 2015)
Are you ready for the most awesome LEGO building adventure yet? Journey through six incredible worlds bursting with hundreds of new LEGO approved fan ideas and building tips! Learn how to make a wild west train, outer space aliens, a realistic-looking mobile phone and much, much more. Create your own amazing models with step by step guides that unloack the secrets of great LEGO building!